Associations Between Muscle Strength, Glomerular Filtration Rate, And Fall Risk: Insights From The Morse Fall Scale - Sim, Alfred Sutrisno; Santoso, Alexander Halim; Teguh, Stanislas Kotska Marvel Mayello; Pranata, Catherine Christiana; Soeltanong, Dianova (Pusat Riset dan Inovasi Nasional, 2025)
Falls among older adults and individuals with chronic conditions pose a major public health concern, leading to injuries, reduced quality of life, and increased healthcare costs. Identifying modifiable risk factors is crucial for prevention. Muscle strength, particularly in the lower extremities, and renal function, measured by glomerular filtration rate (GFR), are potential predictors of fall risk. Sarcopenia and chronic kidney disease (CKD) exacerbate muscle weakness, impairing balance and mobility. While the Morse Fall Scale (MFS) assesses clinical and environmental risks, it lacks physiological measures like muscle strength and renal function. This study aims to bridge this gap by examining associations between muscle strength, GFR, and fall risk, enhancing fall risk assessments and contributing to a more comprehensive understanding of fall prevention. This cross-sectional study at Bina Bakti Nursing Home was done in 2024 examined muscle strength, GFR, and fall risk in 93 elderly (≥60 years). Participants provided consent; those with incomplete data were excluded. Partial correlation analysis showed strong right-left grip strength correlation (p < 0.001) but no significant associations with Morse Fall Scale scores (p = 0.058, p = 0.093), suggesting grip strength alone poorly predicts fall risk. This study confirms grip strength as a reliable muscle function measure but not a strong fall risk predictor. Age plays a dominant role, necessitating fall prevention strategies integrating balance, mobility, cognition, and environment. Renal function did not directly influence fall risk but may contribute indirectly through frailty, warranting further investigation.